Kasus Gizi Buruk pada An. MFA dengan Pendekatan Kedokteran Keluarga di Wilayah Kerja Puskesmas Gembong, Kecamatan Balaraja, Kabupaten Tangerang, Provinsi Banten Periode: 10 November 2022 – 12 Desember 2022 - Felix Ongko; Cindy Willyana; Melly Liman; Zita Atzmardina (Malahayati Nursing Journal, 2023)
ABSTRACT Malnutrition (severe wasting) is a state of malnutrition caused by insufficient intake or increased demand/output or both simultaneously. Globally, one in five children under the age of 5 die from malnutrition. Based on the World Health Organization (WHO) in 2022, Indonesia is in the second highest cases of malnutrition out of 84 countries. Based on Riset Kesehatan Dasar Indonesia in 2018, stated that 10.2% toddlers were undernourished and 3.5% toddlers were malnourished. In 2022 the number of toddlers with malnutrition at the Gembong Health Center is 5 toddlers, which is decrease compared to 2021, which is 6 toddlers. Improvement nutritional status of Child MFA thereby increasing growth and development optimally. A family medicine approach with the Mandala of Health paradigm was carried out in a child aged 1 year and 7 months came to the Gembong Health Center to control post-hospitalization of bronchopneumonia and improve malnutrition. During the physical examination and anthropometry plotted on the WHO curve, it was found that the weight/height was below -3 SD so it was categorized as severe wasting. At the time of the visit, the factors that caused the patient's condition were lack of appetite, irregular diet, less varied food menu and lack of knowledge of the patient's parents regarding the child's nutritional needs and malnutrition. After the intervention, an increase in body weight (BB) and height (TB) was obtained. Based on a comprehensive and holistic approach to Child MFA, there is an increase in BB and TB in An.MFA so that it is expected that the quality of life of An.MFA is better. Keywords: Family Medicine, Mandala of Health, Severe Wasting  ABSTRAK Gizi buruk (severe wasting) merupakan keadaan malnutrisi yang disebabkan oleh asupan yang kurang atau kebutuhan/keluaran yang meningkat atau keduanya secara bersamaan. Secara global, satu dari lima anak di bawah usia 5 tahun meninggal akibat gizi buruk. Berdasarkan World Health Organization (WHO) tahun 2022, Indonesia menempati urutan kedua kasus gizi buruk tertinggi dari 84 negara. Riset Kesehatan Dasar Indonesia Tahun 2018 menyatakan bahwa terdapat 10,2% balita dengan gizi kurang dan 3,5% baalita dengan gizi buruk. Tahun 2022 jumlah balita dengan gizi buruk di Puskesmas Gembong sebanyak 5 balita dimana jumlah ini berkurang dibanding dengan tahun 2021 sebanyak 6 balita. Perbaikan status gizi An.MFA sehingga meningkatkan pertumbuhan dan perkembangan secara optimal. Dilakukan pendekatan kedokteran keluarga dengan paradigma Mandala of Health pada seorang anak usia 1 tahun 7 bulan datang ke Puskesmas Gembong dengan keluhan ingin kontrol post rawat inap bronkopneumonia dan perbaikan gizi buruk. Saat dilakukan pemeriksaan fisik dan antropometri yang di plotting dalam kurva WHO didapatkan BB/TB di bawah -3 SD sehingga dikategorikan sebagai gizi buruk. Pada saat dilakukan kunjungan ditemukan bahwa faktor yang menyebabkan kondisi pasien adalah kurangnya nafsu makan, pola makan yang tidak teratur, menu makanan yang kurang bervariasi serta kurangnya pengetahuan orang tua pasien mengenai kebutuhan gizi anak dan gizi buruk. Setelah dilakukan intervensi maka didapatkan peningkatan berat badan (BB) dan tinggi badan (TB). Setelah dilakukan pendekatan komprehensif dan holistik pada An.MFA terjadi peningkatan BB dan TB pada An.MFA sehingga diharapkan kualitas hidup An.MFA lebih baik. Kata Kunci: Kedokteran Keluarga, Mandala of Health, Gizi Buruk